The final stand : a Colonial Fleet novel - Campbell, Rick (Navy Commander) (Nexus House, 2025)
"The human colonies throughout the galaxy have been decimated by the relentless assault of the Korilian Empire, leaving Earth as the final refuge. Humankind's last hope rests on the tactical prowess of Admiral Jon McCarthy and the foresight of the Nexus House, an ancient conclave of clairvoyants who have long guided humanity's path. With the destruction of Earth nearing, the discovery of Lara Anderson, a woman with the rare and forbidden ability to read minds, offers a glimmer of hope. Against all protocols, Rhea Sidener, the visionary leader of the Nexus House, chooses to harness Lara's abilities, believing her to be the key to altering the course of the war."--